Pengaruh Konseling Apoteker Terhadap Kepatuhan Penggunaan Obat Antidiabetes dan Kontrol Glikemik pada Pasien Diabetes - Hayatun Nufus; Aminah Dalimunthe; Wiryanto Wiryanto (Fakultas Farmasi Universitas Andalas, 2025)
Controlling blood glucose is paramount in diabetes management, yet medication non-adherence often hinders optimal outcomes. This study investigated the impact of pharmacist counseling on Fasting Blood Glucose (FBG) levels and medication adherence in Type 2 Diabetes Mellitus (T2DM) patients within a rural primary healthcare setting. A quasi-experimental pre- and post-test design was employed with 112 T2DM outpatients from Puskemas Simpang Mamplam, Bireuen City, Aceh, Indonesia, from March to April 2024. Medication adherence was assessed using the MARS-10 Questionnaire, and FBG levels were measured via finger prick. The majority of participants were female (79.5%), aged 41-60 (45.5%, mean age 55.70 ± 10.07 years), with secondary education (43.8%), predominantly sedentary/inactive workers (60.7%), and reported low-income (38.4%). Data analysis was performed using the Wilcoxon Signed rank Test. Following counseling, which was provided every two weeks over the two-months period, the mean medication adherence score significantly increased (p < 0.001) from 3.150 ± 0.942 to 8.790 ± 1.297. FBG levels also significantly decreased (p<0.05), from an initial mean of 308.98 ± 72.995 to 220.42 ± 68.547 at two weeks, 162.36 ± 50.191 at four weeks, and 130.00 ± 27.774 at six weeks. These findings suggest that pharmacist counseling significantly improves both medication adherence (p < 0.001) and glycemic control (FBG decrease, p < 0,05) in T2DM patients.